The Effect Of Cocoa Fruit Skin Waste Poc And Npk Fertilizer On The Growth Of Cocoa Seedlings (Theobroma Cacao L.: Pengaruh Poc Limbah Kulit Buah Kakao Dan Pupuk Npk Terhadap Pertumbuhan Bibit Kakao (Theobroma Cacao L.) - Mahdalena; Santiya Patricia; Puteri Aprilani; Asiah Wati (Universitas Widya Gama Mahakam, 2025)
This study aims to determine the effect of liquid organic fertilizer (POC) from cocoa pod waste and NPK fertilizer on the growth of cocoa seedlings. The study was conducted experimentally with a completely randomized design (CRD) consisting of 5 treatments: control (without fertilizer), 100 ml/liter POC, 0.5 g/plant NPK, a combination of low-dose POC + NPK, and a combination of high-dose POC + NPK. The parameters observed included plant height, number of leaves, and stem diameter for 8 weeks. The results showed that the combination of POC from cocoa pod waste and NPK fertilizer had a significant effect on the growth of cocoa seedlings compared to single treatments. The high-dose combination gave the highest growth in all observed parameters. The use of POC from cocoa pod waste can be an environmentally friendly alternative to support the growth of cocoa plants. Keywords: Cocoa, cocoa pod skin POC, NPK fertilizer, seedling growth